If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1y + 2) + 1y = 19(2y + 3) Reorder the terms: 2(2 + 1y) + 1y = 19(2y + 3) (2 * 2 + 1y * 2) + 1y = 19(2y + 3) (4 + 2y) + 1y = 19(2y + 3) Combine like terms: 2y + 1y = 3y 4 + 3y = 19(2y + 3) Reorder the terms: 4 + 3y = 19(3 + 2y) 4 + 3y = (3 * 19 + 2y * 19) 4 + 3y = (57 + 38y) Solving 4 + 3y = 57 + 38y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-38y' to each side of the equation. 4 + 3y + -38y = 57 + 38y + -38y Combine like terms: 3y + -38y = -35y 4 + -35y = 57 + 38y + -38y Combine like terms: 38y + -38y = 0 4 + -35y = 57 + 0 4 + -35y = 57 Add '-4' to each side of the equation. 4 + -4 + -35y = 57 + -4 Combine like terms: 4 + -4 = 0 0 + -35y = 57 + -4 -35y = 57 + -4 Combine like terms: 57 + -4 = 53 -35y = 53 Divide each side by '-35'. y = -1.514285714 Simplifying y = -1.514285714
| -x/6=2x+52 | | 7x+2(4-2x)=-25+6 | | -10m+7=-7+-11 | | 6+6x+6=0 | | 6-8x=5x-8x-9 | | 4(g+1)=16 | | 33.2544-1.278+0.0237x^2=0 | | 2x-9+3x+12=2x+78 | | .7(3)+4.6=7.3-.2(3) | | 16t-7t+4=13 | | 11z-5=-9z+7 | | -4(n-4)=8(-15-9n) | | 12x=-10 | | x^2-3x+3x-4+x+5+x+2=38 | | 2(s+2)=18 | | 6(4z+2)=3(8a+4) | | 6.2h+5-1.4h=3+4.8h+2 | | 4x^2+8x+4=-33 | | -14w+18w=-8 | | 8=4(-x+3) | | .21+4.6=7.3-0.6 | | 0.0237x^2-1.278x+33.2544=0 | | -(r-4)-5(r-7)=4r+6+6r+1 | | -4.3-0.1z=-6.1 | | 6-8x-3x=61 | | 6(u+1)-9=4(4-1)+2u | | 5r^2-45r+100=0 | | X^2=4x+8 | | 26-(x+9)=5x-7 | | -1=9-6.6 | | 7w-6w+3=12 | | 7y-10-2y+9=0 |